Exploring Growth of Gracilaria sp. using the Raft Culture Method - Ilac, Adora Giron; Foronda, Joanna Mae Saoadan; Ayop, Antonio Narollo; Europa-Morales, Anna Liza Villanueva; Ruadap, May Evellia Valencia (Marine Science Department Diponegoro University, 2024)
The seaweed Kawkawayan (Gracilaria sp.), marketed as a food product in the Ilocos Region, has the potential for high profitability due to its growing demand across various industries. The research, conducted in Sinait, Ilocos Sur, used the raft culture method to assess growth by measuring average weight every 15 days and analyzing its relationship with seawater parameters (dissolved oxygen, pH, turbidity, salinity, water current, conductivity, water temperature, and total dissolved solids). The data were analyzed using a descriptive correlation design, employing the Mean and Pearson Product Moment of Correlation. A 3.5 X 5 m raft with six monolines containing 23 seedlings was installed in the culture site. The results indicated that pH, conductivity, TDS, and turbidity were within the normal range, whereas temperature, salinity, DO, and water current were above the average. Gracilaria's weight increased consistently every 15 days, reaching a peak of 22.99 g on the 105th day. However, there was no significant correlation between the weight gain and the measured seawater parameters. The fluctuations in Gracilaria’s weight were linked to thallus breakdown caused by vigorous water movements. The study’s findings should be made available to fisherfolks in the coastal community who cultivate Gracilaria; optimal cultivation of this seaweed can be obtained when disturbances are minimal particularly from February to May thus boosting aquaculture productivity. Alternative cultivation methods like tubular nets and cage systems, along with valuable seaweed species, are recommended. Fisherfolks’ participation is crucial for their success and the future of seaweed farming and marine resource conservation.